Perancangan KMS Berbasis Web Dalam Meningkatkan Kompetensi Wisata Lokal di Indonesia Menggunakan Model SECI - Husna, Miftahul; Saputra, Faiz Rizki; Vurnama, Rival; Sugiarti, Yuni (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2024)
Abstract: Tourism is a dynamic sector that significantly contributes to the global economy, including Indonesia. This study discusses the design of a web-based Knowledge Management System (KMS) to support the development of local tourism, using the SECI model (Socialization, Externalization, Combination, Internalization) as the primary framework for managing the knowledge cycle. The Socialization stage captures tacit knowledge from tourism practitioners through direct interaction and observation. The Externalization stage transforms this tacit knowledge into explicit knowledge in the form of digital guides and information catalogs. In the Combination stage, various explicit knowledge pieces are integrated into a centralized KMS platform. Finally, the Internalization stage enables tourism practitioners to learn and internalize explicit knowledge through online training modules and interactive features. The results demonstrate that applying the SECI model provides a systematic structure for managing local tourism knowledge, enhancing competencies, and expanding the promotional reach of destinations to global markets. In conclusion, this web-based KMS not only supports knowledge management but also strengthens the competitiveness of local tourism in the digital era. Keywords: Digital, KMS, SECI Model, Tourisem, Website.